Organized Crime at Sea: An Examination of 21st Century Pirates, Thugs, and Drug Runners in the Context of Irregular War - De Coster, Jamie Lynn. (2018)
Abstract: Maritime organized criminal groups such as pirates, thugs, and drug runners operate beyond borders and threaten the ocean as a global common. The nature of their tactical activities become complex strategic problems when they threaten international trade, fuel intrastate conflict, compromise regional instability, and enable illicit economies. These groups take advantage of weak state penetration into the physical, political, economic, and social spaces of states, and do so at the local, regional, and international levels. They exploit seams in laws and law enforcement, and characteristically use brutal violence to coerce citizens and elites to comply with their will. Such use of violence increasingly blurs their activities with those of other non-state armed groups such as insurgents and militias. Often, the interests of these profit-seeking groups overlap with those seeking political change, which further increases their threat to states, and requires a public sector response that blends military and law enforcement power. The legal complexities of such a combined response warrants a nuanced understanding of authorities, local laws, and regional mechanisms for cooperation. Through the study of three case studies in Somalia, Nigeria, and Colombia, the author examined three types of maritime crimes using process-tracing, and was informed by theories of irregular war and criminology to explain patterns of these 21st Century maritime criminal groups more broadly. The author deduces four patterns and eight facilitating conditions of maritime organized crime. The concluding recommendation is a "pressure campaign," which incorporates elements of both hard and soft power, applied consistently against the needs of the criminal groups as a more powerful option than military or law enforcement action on its own. Various strategies, tailored to the threat, can evolve from this conceptual construct.; Thesis (Ph.D.)--Tufts University, 2018.; Submitted to the Dept. of Diplomacy, History, and Politics.; Advisor: Richard Shultz.; Committee: Antonia Chayes, and Robert Pfaltzgraff.; Keyword: International relations.